An Overview of On-Farm Hygienic Milk Production (International Journal of Innovative Research in Engineering & Management, 2023)
The dairy sector has adopted hazard analysis  of critical control points (HACCP) systems to ensure the  food safety of dairy products. Through a chain management  strategy, this allows for quality verification of final goods  (European Commission, 2004b). Raw milk's quality and  safety are critical for milk and the dairy products' safety and  quality. Milk contamination with bacteria, chemical  residues, and other pollutants affects the safety and quality  of the products. Microbial contamination is the subject of this chapter. Salmonella spp, Listeria monocytogenes and  Campylobacter jejuni are examples of human microbial  pathogens discovered in raw milk. A very high  microbiological quality of raw milk is essential for  preventing process losses and achieving an optimum shelf  life for dairy products, in addition to its importance for the  public health. For example, faults in semi-hard cheeses are  caused by the spore formers of butyric acid bacteria in the  raw milk, and raw milk contamination with Bacillus cereus  bacteria reduces the shelf life of pasteurized dairy products.  Quality assurance methods for dairy farms are being created,  and bacteriological structures are being used in farms bulk of  raw milk payment systems, in order to guarantee that bulk  tank milk has a high microbiological quality. Furthermore,  dairy producers' sanitary milk production is critical for  animal’s welfare and dairy industry's image. Infections of  pathogenic microorganisms affect cows (e.g., udder tissue,  gastrointestinal tract), resulting in lower milk production and  even mortality. In conclusion, all components of the dairy  production chain benefit from the management of the  microbial ecology at the dairy farm, which leads to on-farm  hygienic milk productions.
Keywords: Dairy Products; Lactose; Milk; Pasteurized